Hygrothermal Aging History of Amine-Epoxy Resins: Effects on Thermo-Mechanical Properties - Gibhardt, Dennis; Buggisch, Christina; Meyer, Devin; Fiedler, Bodo (Frontiers in Materials, 2022)
Epoxy systems are widely used as matrix resins for fiber reinforced polymers (FRP) and, therefore, often have to withstand harsh environmental conditions. Especially in marine and offshore environments moisture or direct water contact lead to water absorption into the epoxy resin. As a result, the mechanical properties change during application. Since diffusion at room or colder temperatures is slow, industry and academia typically use accelerated aging methods at elevated temperatures for durability prediction. However, as the water-polymer interaction is a complex combination of plasticization, physical aging, and molecular interaction, all of these mechanisms are expected to be affected by the ambient temperature. To reveal the impact of aging time and temperature on the thermo-mechanical properties of an amine-epoxy system, this publication includes various hygrothermal aging conditions ranging from 8 °C to 70 °C. Thus, it is demonstrated via long-term aging, DMTA and FTIR investigations that, e.g. strength, stiffness, strain to failure and the glass transition temperature (Tg) can differ significantly depending aging time and temperature. For example, it can be shown that water absorption at cold temperatures leads to the strongest and longest-lasting reduction in strength, although the maximum water absorption amount is lower than at higher temperatures. For the application, this means that strength differences of up to 26 % can be obtained, depending on the aging method selected. Furthermore, it can be shown that conventional prediction models, such as Eyring correlation, which consider the mobility of the molecular structure for the prediction of thermo-mechanical properties, can only be used to a limited extent for prediction in hygrothermal aging. The reasons for this are seen to be, in particular, the different characteristics of the water-polymer interactions depending on the aging temperature. While plasticization dominates in cold conditions, relaxation and strong water-molecule bonds predominate in warm conditions.